(untitled) (PANGEEA, 2025)
The Metaliferi Mountains are located in the southern area of the Apuseni Mountains. In these mountains there are the most important gold and silver deposits in Romania and Europe. An unusual feature of the gold-silver mineralization is the presence of gold and silver tellures, discovered for the first time in the deposits in the “golden quadrangle” Brad - Săcărmb - Roşia Montană - Baia de Arieş. In this study there are some clarifications regarding the genesis of these mineralizations and the effects of local tectonics and geology on the formation of gold and silver deposits.